Effectiveness of Exercise on Sleep Quality in Attention Deficit Hyperactivity Disorder: A Systematic Review and Meta-Analysis - Daniel González-Devesa; Miguel Adriano Sanchez-Lastra; Benito Outeda-Monteagudo; José Carlos Diz-Gómez; Carlos Ayán-Pérez (Children)
Objective: This study aimed to systematically review the available evidence on the effects of exercise training programs on sleep quality in attention deficit hyperactivity disorder. Methods: Studies were searched in five electronic databases until March 2024. The methodological quality of the included studies was assessed using the Physiotherapy Evidence Database and Methodological Index for Non-Randomized Studies scales. Results: A total of five randomized clinical trials, two non-randomized comparative studies, and one single-arm trial were included. Self-reported sleep quality (n = 7) and objective sleep status (n = 3) were the main outcomes analyzed. Generally, exercise induced positive effects on self-reported sleep outcomes. The performed meta-analysis with data from 131 participants indicated that exercise showed a non-significant trend towards increasing objective sleep duration (Hedges’ g −2.67; 95% CI −11.33; 5.99, p = 0.185). While exercise appears safe for individuals with attention deficit hyperactivity disorder, its efficacy in managing sleep disturbances in this population remains uncertain. Conclusions: While there is evidence suggesting a positive impact of exercise on self-reported sleep quality, its efficacy for improving sleep duration could not be confirmed.